INFLUENCE OF CULTURAL FACTORS ON CHOICE OF CHILDBIRTH PLACE AMONG WOMEN IN OYIGBO LOCAL GOVERNMENT AREA, RIVERS STATE, NIGERIA - Ngozi Afulenu Obika-Ndiri; Chizoma Millicent Ndikom; Ogochukwu Immaculate Obika; Omineokuma Tubonemi Aseminaso (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
BACKGROUND: Some cultural practices which encourages both maternal mortality and infant death, are still a major challenge especially in developing countries like Nigeria, cultural norms and practices during childbirth are common but little is documented about how these cultural and religious beliefs influence women and their childbirth place choices. The aim of this study was to find out the prevalent cultural factors that influence the choice of childbirth places among the women of child bearing age, in Oyigbo Local Government area of Rivers State in Nigeria. METHODOLOGY: A self-structured questionnaire was used as instrument to collect data for the study through simple random sampling, and these data was analyzed using Frequency and percentage for descriptive statistics while chi-square was used for inferential statistics at 0.05 level of significance. RESULT: The result showed that most of the women had secondary education and were mostly influenced by patriarchal system, and also there was a high level of hospital adherence among the women in Oyigbo. The influence of cultural factors; family traditions (x² = 12.56, p = 0.006), religious beliefs (x² = 70.66, p = 0.000), Lack of confidence in health facilities (x² = 367.83, p = 0.000), and Presence of male skilled birth attendants (x² = 50.85, p = 0.000), were statistical significant to the choice of childbirth place while patriarchal system (x² = 2.99, p = 0.393) was not statistically significant to the choices of childbirth places of women in Oyigbo. Influence of religion (x² = 125.46, p = 0.000) on choices childbirth place was statistically significant. CONCLUSION: Therefore, this study has shown that there is significant religious and cultural influence on the choices of childbirth places of women in Oyigbo Local Government Area of Rivers State. KEYWORDS: Birthplace, Childbirth, Maternal Mortality, Oyigbo, Women’s health